Tunable photonic microwave filters based on Opto-VLSI processors - Xiao, F.; Juswardy, Budi; Alameh, K. (2009)
A tunable photonic microwave filter structure utilizing an opto-very-large scale integration (opto-VLSI) processor is proposed and experimentally demonstrated. The opto-VLSI processor slices a radio-frequency (RF)-modulated wideband light source into wavebands of arbitrary weights and incremental delay times to realize a tunable RF filter response. Experimental results demonstrate a tunable microwave filter that can simply be reconfigured with high flexibility via a software-driven opto-VLSI processor. Theoretical simulations are in good agreement with the experimental results. © 2009 IEEE.